Exchange transfusion activates coagulation and alters the coagulation profile in newborn infants - Långström, Satu; Wartiovaara-Kautto, Ulla; Andersson, Sture; Heikinheimo, Markku; Petäjä, Jari (Thrombosis and Haemostasis, 2006)
Exchange transfusion (ET) with adult blood is a standard procedure for neonates with severe hyperbilirubinemia. How ET affects newborn coagulation system remains, however, largely unknown. Thus, we prospectively evaluated the effect of ET on thrombin formation and coagulation profile in 18 newborns (22 ETs). Prothrombin fragment F1+2 and thrombin-antithrombin complexes increased considerably during ET while platelets were significantly reduced. Protein C increased less (p<0.001) and factorVIIIc more (p<0.001) than expected based on their levels in the infused blood. Further, in vitro thrombin generation initiated by5 pM tissue factor was analysed. Before the first ET, newborn endogenous thrombin potential (ETP) and thrombin peak remained at ≈60% of adult control plasma levels, but the lag time to thrombin burst in newborn plasma was ≈45% shorter than the lag time in adult plasma. At the end of the first ET, the thrombin burst still started ≈35% earlier in newborn than adult plasma, whereas ETP and thrombin peak were increased to >90% of adult levels. ETP and peak remained elevated at adult levels until the beginning of the second ET. APC-induced reductions in newborn ETP remained unaltered throughout the first ET. The reductions of ETP by APC were less pronounced in newborn than adult plasma (p<0.0001).We conclude that ET is associated with multiple procoagulant changes and increased in vivo thrombin formation. This ET-induced procoagulant challenge may be of clinical significance in sick newborns already prone to bleeding and thrombotic complications.
Keywords: Blood coagulation; exchange transfusion; newborn; protein C; thrombin